Genesis and Identity of Chanco Cheese (Chile 1750-1860). a Contribution to Studies on Appellations of Origin in Latin America [Génesis E Identidad del Queso Chanco (Chile 1750-1860). Una Contribución Al Estudio de Las Denominaciones de Origen en América Latina] - Lacoste, P; Soto-González, N (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2014)
The origin of Chanco cheese in Chile, between 1750 and 1860, is discussed. The inventories of eight cheese factories from the 18th and 19th centuries as well as additional documentary sources from the time period are studied. Chanco cheese was a cooked and matured cheese from cow and, mainly, sheep milk. The original productive zone was limited by the Maule and Itata rivers, in the Central Valley. In the 18th and 19th centuries, Chanco cheese was recognized as the best cheese in Chile; its production and marketing were well established during the first two thirds of the19th century, and it commanded good market prices based on its fame. Chanco cheese was eaten throughout almost the entire country, from Copiapó to Valdivia. Chanco cheese was also significantly exported during the middle of the 19th century. © 2014, Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal. All Rights reserved.